Effect of semaglutide on liver enzymes and markers of inflammation in subjects with type 2 diabetes and/or obesity - Newsome, Philip; Francque, Sven; Harrison, Stephen; Ratziu, Vlad; Van Gaal, Luc; Calanna, Salvatore; Hansen, Morten; Linder, Martin; Sanyal, Arun (Alimentary pharmacology & therapeutics, 2019)
Summary Background Obesity and type 2 diabetes are drivers of non‐alcoholic fatty liver disease (NAFLD). Glucagon‐like peptide‐1 analogues effectively treat obesity and type 2 diabetes and may offer potential for NAFLD treatment. Aim To evaluate the effect of the glucagon‐like peptide‐1 analogue, semaglutide, on alanine aminotransferase (ALT) and high‐sensitivity C‐reactive protein (hsCRP) in subjects at risk of NAFLD. Methods Data from a 104‐week cardiovascular outcomes trial in type 2 diabetes (semaglutide 0.5 or 1.0 mg/week) and a 52‐week weight management trial (semaglutide 0.05‐0.4 mg/day) were analysed. Treatment ratios vs placebo were estimated for ALT (both trials) and hsCRP (weight management trial only) using a mixed model for repeated measurements, with or without adjustment for change in body weight. Results Elevated baseline ALT (men >30 IU/L; women >19 IU/L) was present in 52% (499/957) of weight management trial subjects. In this group with elevated ALT, end‐of‐treatment ALT reductions were 6%‐21% (P<0.05 for doses≥0.2 mg/day) and hsCRP reductions 25%‐43% vs placebo (P < 0.05 for 0.2 and 0.4 mg/day). Normalisation of elevated baseline ALT occurred in 25%‐46% of weight management trial subjects, vs 18% on placebo. Elevated baseline ALT was present in 41% (1325/3268) of cardiovascular outcomes trial subjects. In this group with elevated ALT, no significant ALT reduction was noted at end‐of‐treatment for 0.5 mg/week, while a 9% reduction vs placebo was seen for 1.0 mg/week (P = 0.0024). Treatment ratios for changes in ALT and hsCRP were not statistically significant after adjustment for weight change. Conclusions Semaglutide significantly reduced ALT and hsCRP in clinical trials in subjects with obesity and/or type 2 diabetes.